Pemberdayaan Wisata Bamboe Wanadesa melalui Praktek Keberlanjutan - Miswaty, Miswaty; Ariani, Misna; Latumeten, Anna Anganita Theresia; Anugrah, Malik; Nabilla, Prety (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
The Community Partnership Empowerment Program of the 2024 DRTPM grant runs for eight months starting from June 2024. Community partnership empowerment at Wisata Bamboe Wanadesa is carried out by a PKM team consisting of lecturers from Balikpapan University and two students. This PKM aims to help Wisata Bamboe Wanadesa manage its organization sustainably. Wisata Bamboe Wanadesa is located on Jalan Giri Rejo Km 15 RT.26, Karang Joang Village, Balikpapan Utara District, Balikpapan City, East Kalimantan Province. This tourist attraction is based on nature tourism with bamboo forests as its main icon and is surrounded by the Manggar reservoir in Balikpapan City. The Balikpapan University lecturer team provided sustainable tourism management training to members of the Bamboe Wanadesa tourism management in the form of socialization of waste sorting and processing waste into compost as well as training in processing bamboo leaves into cookies and bamboo leaf tea. The results of the community service activities showed that the members were very enthusiastic and actively discussed with the speakers. Eighty percent of the participants have understood the contents of the training material and followed up by practicing waste sorting and processing bamboo leaves into cookies and bamboo leaf tea.